2013
DOI: 10.1371/journal.pone.0069241
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the Prevalence of Opioid Diversion by “Doctor Shoppers” in the United States

Abstract: BackgroundAbuse of prescription opioid analgesics is a serious threat to public health, resulting in rising numbers of overdose deaths and admissions to emergency departments and treatment facilities. Absent adequate patient information systems, “doctor shopping” patients can obtain multiple opioid prescriptions for nonmedical use from different unknowing physicians. Our study estimates the prevalence of doctor shopping in the US and the amounts and types of opioids involved.Methods and FindingsThe sample incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
71
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 96 publications
(72 citation statements)
references
References 30 publications
0
71
0
1
Order By: Relevance
“…Observational Studies in Epidemiology (STROBE) Statement Checklist for Observational, Population-Based Cohort Studies [26,27].…”
Section: Comprehensiveness Of Reporting (Bb Only) According To the Stmentioning
confidence: 99%
See 2 more Smart Citations
“…Observational Studies in Epidemiology (STROBE) Statement Checklist for Observational, Population-Based Cohort Studies [26,27].…”
Section: Comprehensiveness Of Reporting (Bb Only) According To the Stmentioning
confidence: 99%
“…Many studies did not report basic cohort details including sex (20), age (18) and/or cohort size (8). Studies did not identify how they managed any bias (26), loss to follow up (39), missing data (39) or sensitivity analyses (38). Furthermore, 21 studies did not report the funding source.…”
Section: Comprehensiveness Of Reporting Observational Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Kenan and colleagues [7] found that the number of opioid prescriptions per 100 persons increased by 35.2% between 2000 and 2009, and the average size of an oxycodone and hydrocodone prescription increased by 69.7% and 69.4%, respectively, during the same period. For 146 million opioids dispensed, 0.7% of purchasers accounted for 1.9% of all opioid prescriptions, and higher opioid dosage correlated with a higher risk of overdose [8].…”
Section: Introductionmentioning
confidence: 99%
“…Doctor shoppers were found to have an increased number of prescriptions, higher number of pills, and higher number of morphine equivalents [4]. The work of McDonald and Carlson [8] in 2008 found that patients who were diverting opioids had an average of 32 prescriptions from 10 providers.…”
Section: Introductionmentioning
confidence: 99%